If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3x + -1) + -2x + 5 = 121 Reorder the terms: -4(-1 + 3x) + -2x + 5 = 121 (-1 * -4 + 3x * -4) + -2x + 5 = 121 (4 + -12x) + -2x + 5 = 121 Reorder the terms: 4 + 5 + -12x + -2x = 121 Combine like terms: 4 + 5 = 9 9 + -12x + -2x = 121 Combine like terms: -12x + -2x = -14x 9 + -14x = 121 Solving 9 + -14x = 121 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -14x = 121 + -9 Combine like terms: 9 + -9 = 0 0 + -14x = 121 + -9 -14x = 121 + -9 Combine like terms: 121 + -9 = 112 -14x = 112 Divide each side by '-14'. x = -8 Simplifying x = -8
| 200.96=3.14*D | | 2a+5b=7 | | 7u/5=42 | | X=1.571428571 | | 400x+200=350x+850 | | 9e^11x=11 | | -3x+-5=2x | | 270.04=3.14*D | | 9(x-9)=-18 | | 2x+76=90 | | 10.50=1.50+2n | | 5(2y-4)=-10 | | 2.6=x/(2-2x) | | 5x+24=3 | | -(-7x-5)+8x-10= | | 2x+5(5x-14)=97 | | 14*20-6(20+3)=20+9 | | 2/3=10/e | | 5x-4x=-6x+4 | | 3(7x+2)(x-1)=0 | | =56x^7+21x^4+63x^3 | | 4(x-1)-3x=-2x-4+3 | | 2(r/3-7)=30 | | 3x^3-8x^2-20x+16=0 | | 7y+26=180 | | 6x+14+90+94=180 | | 10m-13m+5+11m=21 | | 20x=40+10x | | 17j-6j+2j-5j-j=7 | | 0=-12x^2-1560x-48000 | | x/x-8=24-2x/x-8 | | -27=-5x-2(-3+18) |